Late treatment effects following bone marrow transplant: Efficacy of implementing international guidelines. (27th December 2016) - Shanklin, V.E.; Snowden, J.A.; Greenfield, D.M.
Abstract : An increasing cohort of haematopoietic cell transplantation (HCT) survivors has raised awareness of long‐term and late effects. Updated recommendations for HCT late effects screening were published in 2012 [Majhail et al. Biology of Blood and Marrow Transplantation, 18 (2012):348]. We aimed to assess the clinical efficacy of a dedicated screening clinic to identify problems in HCT survivors using the international guidelines. Clinic letters and test results of the first 59 consecutive patients attending the screening clinic were evaluated. 30 females and 29 males (mean age of 49 years, range 22–74) were included. The mean time since transplant was 6 years (0.5–18). 49/65 transplants were allogeneic. Primary indications for HCT were myeloid (56%), lymphoid (37%), solid tumour (5%) and auto‐immune diseases (2%). 134 complications were reported (mean 2, range 0–8), with 114 documented further actions/referrals. The most commonly reported concerns were pain 18/59 (31%), fatigue 14/59 (24%), sexual function 14/59 (24%) and sleep disturbance 11/59 (19%). Second primary malignancies were recorded in five cases. Implementation and audit of the international late effect screening guidelines confirm the need for systematic long‐term physical and psychological screening and care, thus ensuring timely and efficient identification of problems and the opportunity to minimise morbidity effects and optimise health.